THE EFFECTS OF SCRAPPING TREATMENT TECHINIQUES FOR BODY HEALTH - Fariz Fadly Tanjung (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Scraping treatment techniques are often referred to treatment that is simple and easy but has a healing effect which is quite fast compared to modern medicine. For the Javanese in particular, alternative treatment techniques through the scrapings considered more practical, inexpensive, rational, effective and proven. But actually what are the effects of this scraping treatment techniques so that becoming popular and able to survive in modern times. Kerokan or in modern medical termsis referred to scraping the skin with a body scrub that has a dull surface to redness on the skin. Scrapings treatment technique is not only well known in Java, in some other countries especially in Southeast Asia,many believes in the efficacy of the scrapings. Through histopathology, assessed whether there is damage to the skin and an increased in the volume of blood flow and hormone levels or chemical mediators in the body or not by scrapings experience. The results of several studies showed they are no damage to the skin, but local acute inflammatory occurs as normal reaction. There is an increasing blood flow perfusion due to the increased of metabolism rate. Biomolecular studies showed an increased in IL-1, C1q and β-endorphin as well as decreased in C3 and PGE2. [J Agromed Unila 2014; 1(1):67-71] Keywords: biomolecular, histopathology, inflamation, scrapping